Associations of fetuin-A level with vascular disease in hemodialysis patients with or without type II diabetes mellitus - Amani K Mohamed; Amany M Abdallah; Maha A Hassan; Nagwa A Mohammed; Solaf A Kamel (SpringerOpen, 2013)
Introduction Fetuin-A is a circulating inhibitor of calcium deposition in the vasculature and may be involved in the pathogenesis of cardiovascular disease. Low plasma fetuin-A level is independently associated with increased risk for cardiovascular disease mortality among men and women without diabetes; in addition, low level of fetuin-A is linked to mortality in patients on dialysis. Aim of the study The aim of the study was to investigate the role of fetuin-A as a marker for microvascular and macrovascular diseases in a high-risk population of end-stage renal disease patients on dialysis, with and without diabetes mellitus. Patients and methods This study included 30 end-stage renal disease patients on regular hemodialysis, with and without diabetes and 10 age-matched and sex-matched apparently healthy controls. All patients were subjected to careful history-taking, including history of strokes and acute myocardial infarction and thorough physical examinations, and cardiac assessment was performed using ECG and ECHO. Routine laboratory tests were performed, such as hemoglobin, fasting blood glucose, serum creatinine, serum urea, serum Na, serum K, uric acid, serum cholesterol, serum triglycerides, serum aspartate aminotransferase, serum alanine aminotransferase, serum albumin, serum calcium, serum phosphorus, intact parathyroid hormone (iPTH), serum iron, total iron binding capacity (TIBC), and serum fetuin-A. Results The study showed significant statistical decrease in serum fetuin-A level in chronic renal failure (CRF) and diabetes patients with vascular strokes when compared with CRF patients and CRF patients with diabetes without history of vascular strokes. There was significant positive correlation between fetuin-A and hemoglobin, serum Ca, serum albumin, TIBC, and total protein (TP), whereas there was significant negative correlation between fetuin-A and serum cholesterol, serum triglyceride (TG), fasting blood glucose (FBG), serum urea, serum creatinine, serum uric acis (UA), iPTH, serum Na, and serum K. No correlation was found between fetuin-A and age or BMI. Conclusion Our findings suggest a unique role for fetuin-A deficiency as a biomarker of vascular diseases in the setting of CRF and type 2 diabetes mellitus.